CAT FLU TREATMENT DUE TO CALICI VIRUS AND HERPES VIRUS INFECTION IN MIXED DOMESTIC CATS - Dominika, Kevin; Arjentinia, Putu Gede Yudhi; Suartha, I Nyoman (Buletin Veteriner Udayana, 2024)
Feline Calicivirus (FCV) and Feline Herpesvirus (FHV) are the most common viral agents that affect cats globally. FCV and FHV can cause respiratory disorders in infected cats. This study aims to present the therapeutic results in mixed-breed domestic cats experiencing chronic feline flu due to FCV and FHV infections. The examinations conducted include physical examinations, routine hematology, radiography, cytology, and rapid tests for FCV and FHV. Cats exhibited symptoms of frequent sneezing accompanied by red-tinged mucus discharge and coughing during the physical examination. Routine hematology results showed leukocytosis, neutrophilia, and eosinophilia in cats. Radiographic examination with X-rays revealed bronchopneumonia in cats. Cytological examination indicated a significant infiltration of neutrophils, lymphocytes, and plasma cells. Rapid tests for FCV and FHV showed that the cats were positive for FCV and FHV antigens. On the 14th day, the cats showed symptomatic improvement after treatment with cefadroxil antibiotics (22 mg/kg BW; q24 hours; orally), dexamethasone (0.5 mg; q12 hours; orally), dexchlorpheniramine maleate (2 mg; q12 hours; orally), bromhexine HCl (1 mg/kg BW; q12 hours; orally), and vitamin B complex (1 tablet; q24 hours; orally). Further research is needed on the incidence rate of coinfection between Feline Calicivirus and Feline Herpesvirus in Bali.